A Novel Xenomonitoring Technique Using Mosquito Excreta/Feces for the Detection of Filarial Parasites and Malaria. - Nils Pilotte; Weam I Zaky; Brian P Abrams; Dave D Chadee; Steven A Williams (Public Library of Science (PLoS), 2016)
BACKGROUND:Given the continued successes of the world's lymphatic filariasis (LF) elimination programs and the growing successes of many malaria elimination efforts, the necessity of low cost tools and methodologies applicable to long-term disease surveillance is greater than ever before. As many countries reach the end of their LF mass drug administration programs and a growing number of countries realize unprecedented successes in their malaria intervention efforts, the need for practical molecular xenomonitoring (MX), capable of providing surveillance for disease recrudescence in settings of decreased parasite prevalence is increasingly clear. Current protocols, however, require testing of mosquitoes in pools of 25 or fewer, making high-throughput examination a challenge. The new method we present here screens the excreta/feces from hundreds of mosquitoes per pool and provides proof-of-concept for a practical alternative to traditional methodologies resulting in significant cost and labor savings. METHODOLOGY/PRINCIPAL FINDINGS:Excreta/feces of laboratory reared Aedes aegypti or Anopheles stephensi mosquitoes provided with a Brugia malayi microfilaria-positive or Plasmodium vivax-positive blood meal respectively were tested for the presence of parasite DNA using real-time PCR. A titration of samples containing various volumes of B. malayi-negative mosquito feces mixed with positive excreta/feces was also tested to determine sensitivity of detection. Real-time PCR amplification of B. malayi and P. vivax DNA from the excreta/feces of infected mosquitoes was demonstrated, and B. malayi DNA in excreta/feces from one to two mf-positive blood meal-receiving mosquitoes was detected when pooled with volumes of feces from as many as 500 uninfected mosquitoes. CONCLUSIONS/SIGNIFICANCE:While the operationalizing of excreta/feces testing may require the development of new strategies for sample collection, the high-throughput nature of this new methodology has the potential to greatly reduce MX costs. This will prove particularly useful in post-transmission-interruption settings, where this inexpensive approach to long-term surveillance will help to stretch the budgets of LF and malaria elimination programs. Furthermore, as this methodology is adaptable to the detection of both single celled (P. vivax) and multicellular eukaryotic pathogens (B. malayi), exploration of its use for the detection of various other mosquito-borne diseases including viruses should be considered. Additionally, integration strategies utilizing excreta/feces testing for the simultaneous surveillance of multiple diseases should be explored.